2009
DOI: 10.1111/j.1462-2920.2009.01978.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term microbial and physico‐chemical variability in low‐temperature hydrothermal fluids near 5°S on the Mid‐Atlantic Ridge

Abstract: This study examines the representativeness of low-temperature hydrothermal fluid samples with respect to their chemical and microbiological characteristics. Within this scope, we investigated short-term temporal chemical and microbial variability of the hydrothermal fluids. For this purpose we collected three fluid samples consecutively from the same spot at the Clueless field near 5 degrees S on the southern Mid-Atlantic Ridge over a period of 50 min. During sampling, the temperature was monitored online. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 62 publications
2
64
0
Order By: Relevance
“…16S rRNA genes were PCR amplified using the primers 27 F and 1492 R (Lane, 1991) and the conditions described previously (Perner et al, 2009). Details on the cloning for genes have been described before (Perner et al, 2009).…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…16S rRNA genes were PCR amplified using the primers 27 F and 1492 R (Lane, 1991) and the conditions described previously (Perner et al, 2009). Details on the cloning for genes have been described before (Perner et al, 2009).…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…16S rRNA genes were PCR amplified using the primers 27 F and 1492 R (Lane, 1991) and the conditions described previously (Perner et al, 2009). Details on the cloning for genes have been described before (Perner et al, 2009). For sequencing of both DNA strands of the 16S rRNA genes from SP-41 and TH-55, the primers 27 F, 1492 R, 562 (5 0 -TAA TCT TGC GAC CGT ACT CC-3 0 ), 719 (5 0 -CTG ACG CTG AGG TGC GAA AG-3 0 ) and 1149 (5 0 -CCC AGT GTG GCT GAT CAT CC-3 0 ) were used.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 200 ml of hydrothermal fluids were concentrated onboard on a 0.2 mm polycarbonate filter and kept at À 20 1C. Detailed sampling procedures and information on the sampling site are described elsewhere (Perner et al, 2007(Perner et al, , 2009(Perner et al, , 2013.…”
Section: Sampling Of Hydrothermal Fluidsmentioning
confidence: 99%
“…These studies demonstrated the prevalence of Gammaproteobacteria, Deltaproteobacteria, Epsilonproteobacteria, Bacteroidetes, Firmicutes, and various candidate divisions in the hydrothermal system. Due to fluctuations in the environmental conditions, microbial communities in hydrothermally influenced regions exhibit variability on various spatial and temporal scales, including large-scale intra-and inter-field variability (Flores et al 2012;Huber et al 2010;Nunoura and Takai 2009), short-term temporal and spatial variability (Perner et al 2009(Perner et al , 2013, and spatial variability on a small scale of a few centimeters to meters (Nakagawa et al 2005;Takai et al 2004). However, most studies focused on the variability of specific microbial populations in the zone adjacent to hydrothermal vents.…”
Section: Introductionmentioning
confidence: 99%